Peran Dinas Perpustakaan Dan Kearsipan Dalam Meningkatkan Minat Baca Pada Pelajar Di Kota Pekanbaru - Aldi Yulien; Abdul Sadad (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research aims to find out and explain the role of the library and archives service in increasing reading interest among students in Pekanbaru City and the inhibiting factors in increasing reading interest among students in Pekanbaru City. The theory used in this research is the role form theory from Jam Ife and Frank Tesoriero (2014) which is divided into four role forms, namely (1) Facilitative Role, (2) Educational Role, (3) Representative Role, (4) Technical Role. The type of research used is descriptive qualitative, data collection techniques obtained through observation, interviews and documentation. The results of this research show that in its facilitative role the library service has and is implementing innovations and work programs which are expected to increase students' interest in reading, namely active school literacy programs, digital library applications and also burning innovations (reading out loud). In its educational role, the department regularly carries out visits or outreach to existing schools. During these visits, the department will socialize about interest in reading to students and conduct training to school libraries where library training is available, such as evaluating whether the school library is appropriate or not with the provisions of a good library. In the role of representatives of the Pekanbaru library and archives department, they have collaborated with schools in Pekanbaru in order to increase students' interest in reading, namely by regularly making visits to schools in turn and during these visits the department will carry out outreach and also take the library car around. and for other collaborations, namely with other departments. In a technical role, it is known that the library service has human resources who are skilled in processing existing data. The inhibiting factors in increasing students' interest in reading are the lack of facilities and book collections in school libraries, and the lack of human resources such as librarians in managing the libraries in each school.